Post-traumatic stress disorder dimensions and asthma morbidity in World Trade Center rescue and recovery workers. (9th August 2017) - Mindlis, I.; Morales-Raveendran, E.; Goodman, E.; Xu, K.; Vila-Castelar, C.; Keller, K.; Crawford, G.; James, S.; Katz, C. L.; Crowley, L. E.; de la Hoz, R. E.; Markowitz, S.; et al.
ABSTRACT: Objective : Using data from a cohort of World Trade Center (WTC) rescue and recovery workers with asthma, we assessed whether meeting criteria for post-traumatic stress disorder (PTSD), sub-threshold PTSD, and for specific PTSD symptom dimensions are associated with increased asthma morbidity. Methods : Participants underwent a Structured Clinical Interview for Diagnostic and Statistical Manual to assess the presence of PTSD following DSM-IV criteria during in-person interviews between December 2013 and April 2015. We defined sub-threshold PTSD as meeting criteria for two of three symptom dimensions: re-experiencing, avoidance, or hyper-arousal. Asthma control, acute asthma-related healthcare utilization, and asthma-related quality of life data were collected using validated scales. Unadjusted and multiple regression analyses were performed to assess the relationship between sub-threshold PTSD and PTSD symptom domains with asthma morbidity measures. Results : Of the 181 WTC workers with asthma recruited into the study, 28% had PTSD and 25% had sub-threshold PTSD. Patients with PTSD showed worse asthma control, higher rates of inpatient healthcare utilization, and poorer asthma quality of life than those with sub-threshold or no PTSD. After adjusting for potential confounders, among patients not meeting the criteria for full PTSD, those presenting symptoms of re-experiencing exhibited poorer quality of life ( p = 0.003). Avoidance was associated with increased acute healthcare use ( p = 0.05). Sub-threshold PTSD was not associated with asthma morbidity ( p > 0.05 for all comparisons). Conclusions : There may be benefit in assessing asthma control in patients with sub-threshold PTSD symptoms as well as those with full PTSD to more effectively identify ongoing asthma symptoms and target management strategies.